Hubungan Pengetahuan Ibu Tentang MP-ASI dengan Status Gizi Baduta: The Relationship between Maternal Knowledge of Complementary Feeding (MP-ASI) and the Nutritional Status of Children Under Two Years (Baduta) - Zulchas, Auliya A’yuni Fitri; Sulistyorini, Chandra; Risnawati, Risnawati; Meihartati, Tuti (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Nutritional status among children under two years (baduta) remains a major public health issue, especially during the First 1000 Days of Life. Inappropriate complementary feeding (MP-ASI) may lead to malnutrition and stunting. Maternal knowledge about MP-ASI is an important factor influencing children’s nutritional status. This study aimed to determine the relationship between maternal knowledge of MP-ASI and the nutritional status of children under two years. This study used a descriptive analytic design with a cross-sectional approach. The study population included all children aged 6–24 months recorded at integrated health posts (Posyandu) in the Teluk Lingga Community Health Center area. A total of 88 respondents were selected using Slovin’s formula and stratified random sampling technique. Data were collected using a structured questionnaire. Data analysis was performed using univariate and bivariate analysis with the Spearman Rank correlation test. The findings showed a statistically significant relationship between maternal knowledge of MP-ASI and the nutritional status of children under two years, with a p-value of 0.030 (p < 0.05). Good maternal knowledge is associated with better nutritional status in children under two years. Therefore, continuous health education is essential to improve maternal knowledge in order to prevent undernutrition, severe malnutrition, and stunting.